2010
DOI: 10.1159/000314999
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Walker-Warburg Syndrome Complicated by Hydrocephalus

Abstract: Walker-Warburg syndrome is a very rare autosomal recessive disorder with congenital muscular dystrophy, brain malformations on the basis of a neuronal migration defect and ocular abnormalities. We report our experience in treating two cases of Walker-Warburg syndrome complicated by hydrocephalus with shunting and endoscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The reason of unsuccessful outcome of previous reported case [14] was unclear. The authors concluded that anatomical distortion might be contributed failure of ETV.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The reason of unsuccessful outcome of previous reported case [14] was unclear. The authors concluded that anatomical distortion might be contributed failure of ETV.…”
Section: Discussionmentioning
confidence: 93%
“…We had high suspicion of aqueduct stenosis on the MRI study, supporting our plan to achieve success utilizing ETV along with CPC. Preuss et al previously reported a single case of hydrocephalus in WWS treated by ETV without CPC [14]. In their case, long term success was not achieved and the patient required placement of ventricle-peritoneal shunt 4 months later.…”
Section: Discussionmentioning
confidence: 99%